Gradients of microstructure, stresses and mechanical properties in a multi-layered diamond thin film revealed by correlative cross-sectional nano-analytics. (April 2019) - Gruber, David P.; Todt, Juraj; Wöhrl, Nicolas; Zalesak, Jakub; Tkadletz, Michael; Kubec, Adam; Niese, Sven; Burghammer, Manfred; Rosenthal, Martin; Sternschulte, Hadwig; Pfeifenberger, Manuel J.; Sartory, Bernhard; et al.
Abstract: Thin diamond films deposited by chemical vapour deposition (CVD) usually feature cross-sectional gradients of microstructure, residual stress and mechanical properties, which decisively influence their functional properties. This work introduces a novel correlative cross-sectional nano-analytics approach, which is applied to a multi-layered CVD diamond film grown using microwave plasma-enhanced CVD and consisting of a ∼8 μm thick nanocrystalline (NCD) base and a ∼14.5 μm thick polycrystalline (PCD) top diamond sublayers. Complementary cross-sectional 30 nm beam synchrotron X-ray diffraction, depth-resolved micro-cantilever and hardness testing and electron microscopy analyses reveal correlations between microstructure, residual stress and mechanical properties. The NCD sublayer exhibits a 1.5 μm thick isotropic nucleation region with the highest stresses of ∼1.3 GPa and defect-rich nanocrystallites. With increasing sublayer thickness, a 110 fibre texture evolves gradually, accompanied by an increase in crystallite size and a decrease in stress. At the NCD/PCD sublayer interface, texture, stresses and crystallite size change abruptly and the PCD sublayer exhibits the presence of Zone T competitive grain growth microstructure. NCD and PCD sublayers differ in fracture stresses of ∼14 and ∼31 GPa, respectively, as well as in elastic moduli and hardness, which are correlated with their particular microstructures. In summary, the introduced nano-analytics approach provides complex correlations between microstructure, stresses, functional properties and deposition conditions. Graphical abstract: Image 10773